Tensões de água no solo e adubações fosfatadas no desenvolvimento do Capim Mombaça - Capucho, Ramon Alexandre (2021)
The objective of this experiment was to analyze the effects of soil water tensions and phosphate fertilization rates on the development, yield and quality of Mombaça grass, under greenhouse conditions. The experiment was carried out in sub-divided plots (4 x 4 x 4), with the soil water tension in four levels in the plots (40, 100, 200 and 300 kPa), in the phosphate fertilization subplots in four levels (100, 200 , 300, 400 kg.ha-1 of P2O5) and in the sub-subplots the cuts in four levels (1st, 2nd, 3rd, 4th cut), in a randomized block design, with four replications. The variables analyzed were: green mass, dry mass, plant height, crude protein, in vitro dry matter digestibility and carrying capacity. All variables evaluated were subjected to analysis of variance, using the F test at the level of 5% probability and when significant for quantitative factors, regression models were used at 5% probability, for the qualitative factor the comparison of means was performed using the Tukey test at 5% probability. There were significant interactions (P<0.05) between the factors under study for the variables: fresh mass, dry mass, plant height, crude protein and carrying capacity. However, only for the variable in vitro digestibility of dry matter, there was no interaction between the studied factors. The treatments with tension of 40 kPa obtained means higher than the others in all studied variables. The doses of P205 were affected as the water deficit increased. For the cut factor, it was observed that the 1st had the best results, followed by the 4th, 2nd and 3rd cuts.